2017
DOI: 10.4330/wjc.v9.i6.547
|View full text |Cite
|
Sign up to set email alerts
|

Entirely subcutaneous defibrillator and complex congenital heart disease: Data on long-term clinical follow-up

Abstract: AIMTo describe the long-term follow-up of patients with complex congenital heart disease who underwent subcutaneous implantable cardiac defibrillator (S-ICD), focusing on local complications, appropriate and inappropriate shocks.METHODSPatients with complex congenital heart disease underwent S-ICD implant in two centers with the conventional technique. Data at follow-up were retrieved from clinical notes and institutional database.RESULTSEight patients were implanted in two centres between 2010 and 2016. Media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Ferro et al. showed similar outcomes in eight patients with S‐ICD and ACHD in the secondary prevention setting . The main reason for this approach was the inability to implant a standard ICD percutaneously.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Ferro et al. showed similar outcomes in eight patients with S‐ICD and ACHD in the secondary prevention setting . The main reason for this approach was the inability to implant a standard ICD percutaneously.…”
Section: Discussionmentioning
confidence: 96%
“…15 Ferro et al showed similar outcomes in eight patients with S-ICD and ACHD in the secondary prevention setting. 16 The main percutaneously. This group showed a similar inappropriate shock rate (12.5%).…”
Section: Discussionmentioning
confidence: 99%
“…No patient had IAS due to over sensing. One patient had an appropriate shock during follow up, and several episodes of self‐terminating VT were noted 34 …”
Section: Discussionmentioning
confidence: 99%
“…54 In another study of eight patients with CHD (seven adults and one child) followed for a median of 2.3 years, there were no inappropriate therapies administered during the entirety of follow-up. 55 Anecdotally, other challenges to S-ICD implantation include patients with dextrocardia, for whom the implantation technique must be mirror-imaged. In addition, patients who have undergone one or more sternotomies may have significant chest wall deformities that make tunneling the lead along the sternum a more challenging task.…”
Section: Subcutaneous Devicesmentioning
confidence: 99%